Chinese Leadership Styles in Public Sector in Tianjin - ZHANG, NAN (2010)
Considerable studies on Chinese leadership styles apply Western models to test Chinese managers, and then define Chinese leadership style with Western ideas. This study assumes that Chinese managers have their own leadership styles distinctive from Westerners and tried to investigate the cultural and historical origin of Chinese leadership style, especially to explore how Confucianism have affected and shaped Chinese leadership style in modern Chinese society. This study adopted a qualitative interview research method ,in which twelve unstructured interviews were conducted with five chief executives and senior managers as well as seven subordinates from five public organizations in Tianjin. By investigating effects of Confucius philosophy on Chinese leadership style , the study not only demonstrated the main demotions of Chinese leadership styles – Guanxi Orientation, paternalism, and heroism, but also highlighted both their contributions and potential issues on shaping and affecting the unique Chinese leadership style. As to the increasing importance of China in global economy and politics, a thorough understanding of the unique Chinese leadership styles will a precondition for management researchers to enhance existing knowledge in this field and to advance cross-cultural managerial efficiencies in modern Chinese society.